Pengaruh Keberadaan Industri Semen terhadap Perubahan Fungsi Lahan, Sosial, dan Ekonomi Masyarakat di Kemukiman Lhoknga, Kabupaten Aceh Besar - Madris; Putra Rizkiya; Zahrul Fuady; Zainuddin Hasan; Myna Agustina Yusuf (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Land-use changes surrounding industrial areas not only have physical impacts on the environment but also create significant social and economic implications for local communities. Changes occurring near cement industry in the Kemukiman Lhoknga, Aceh Besar Regency have transformed land that was previously forest into cement industrial zones, residential areas, and trade and service sectors. This study aims to analyze the influence of the cement industry on changes in land use, as well as the social and economic conditions of the community. Data were collected through primary approaches, including field observations, interviews with local community representatives, and questionnaires distributed to residents, as well as secondary approaches through satellite image interpretation, literature review, and government agency data. The results show an expansion of residential land by 66.38 ha, most of which originated from the conversion of forest land (−80.79 ha) and plantations (−5.10 ha). Social changes were reflected in the shift in community attitudes from initially rejecting to eventually accepting the presence of the cement industry. This change in attitude was driven by economic improvements, marked by expanded employment opportunities and increased community income.